Fostering Autonomy Through Syllabus Design: A Step-by-Step Guide for Success - Alexánder Ramírez Espinosa (Asociación Colombiana de Profesores de Ingles, 2015)
Promoting learner autonomy is relevant in the field of applied linguistics due to the multiple benefits it brings to the process of learning a new language. However, despite the vast array of research on how to foster autonomy in the language classroom, it is difficult to find step-by-step processes to design syllabi and curricula focused on the development of learner autonomy. This paper presents a model of a successful English course, implemented at Universidad del Valle (Colombia), which is expected to serve as a practical guide to articulate the stages of design, implementation, and evaluation of an autonomy-fostering syllabus.